Recent and future trends in synthetic greenhouse gas radiative forcing. Issue 7 (4th April 2014) - Rigby, M.; Prinn, R. G.; O'Doherty, S.; Miller, B. R.; Ivy, D.; Mühle, J.; Harth, C. M.; Salameh, P. K.; Arnold, T.; Weiss, R. F.; Krummel, P. B.; Steele, L. P.; et al.
Abstract: Atmospheric measurements show that emissions of hydrofluorocarbons (HFCs) and hydrochlorofluorocarbons are now the primary drivers of the positive growth in synthetic greenhouse gas (SGHG) radiative forcing. We infer recent SGHG emissions and examine the impact of future emissions scenarios, with a particular focus on proposals to reduce HFC use under the Montreal Protocol. If these proposals are implemented, overall SGHG radiative forcing could peak at around 355 mW m −2 in 2020, before declining by approximately 26% by 2050, despite continued growth of fully fluorinated greenhouse gas emissions. Compared to "no HFC policy" projections, this amounts to a reduction in radiative forcing of between 50 and 240 mW m −2 by 2050 or a cumulative emissions saving equivalent to 0.5 to 2.8 years of CO2 emissions at current levels. However, more complete reporting of global HFC emissions is required, as less than half of global emissions are currently accounted for. Key Points: Measurements of all the major synthetic greenhouse gases have been compiled These measurements have been used to infer recent global emissions trends Based on these trends, future emissions scenarios have been investigated